2006
DOI: 10.1007/s10517-006-0391-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of L-, D-, and DL-carnitine on morphometric parameters of skeletal muscle and exercise performance of laboratory animals receiving carnitine-deficient diet

Abstract: Serum concentration of L-carnitine, the mean thickness of the skeletal muscle fiber, and exercise performance in the forced swimming test decreased in rats receiving a carnitine-deficient diet. Treatment with L-carnitine compensated for carnitine deficiency, while racemate and D-stereoisomer did not increase its level. L-Carnitine, but not racemate and D-stereoisomer, promoted recovery of the skeletal muscle fiber thickness and exercise performance of rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
(12 reference statements)
0
2
0
1
Order By: Relevance
“…Spiering et al [47] showed that carnitine attenuates metabolic stress that occurs after exercise. Numerous studies suggest beneficial effects of increased carnitine intake in reducing physical fatigue and recovery from exercise stress [48,49]. Conversely, some studies have shown no significant positive effects in exercise performance with carnitine [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…Spiering et al [47] showed that carnitine attenuates metabolic stress that occurs after exercise. Numerous studies suggest beneficial effects of increased carnitine intake in reducing physical fatigue and recovery from exercise stress [48,49]. Conversely, some studies have shown no significant positive effects in exercise performance with carnitine [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…Спасова и соавт. [26][27][28] показали, что у здоровых крыс на фоне дефицита левокарнитина возможно развитие жировой дистрофии печени и атрофия скелетных мышц, а также снижение функциональных резервов миокарда и физической работоспособности [26][27][28].…”
Section: левокарнитин в лечении полиморбидных пациентовunclassified
“…There are several other types of carnitine, in which D-carnitine is one of carnitine types. This inactive form may cause a carnitine deficiency in ones body by inhibiting the absorption of other and more useful forms (1). Secondly, acetyl-Lcarnitine is possibly the most effective form for the brain and previous study suggested that it may benefit people with neurodegenerative diseases (2).…”
Section: Introductionmentioning
confidence: 99%